A Method for Simultaneous Echo Planar Imaging of Hyperpolarized (13)C Pyruvate and (13)C Lactate - Reed, Galen D. (2012)
A rapid echo planar imaging sequence for dynamic imaging of [1-(13)C] lactate and [1-(13)C] pyruvate simultaneously was developed. Frequency-based separation of these metabolites was achieved by spatial shifting in the phase-encoded direction with the appropriate choice of echo spacing. Suppression of the pyruvate-hydrate and alanine resonances is achieved through an optimized spectral-spatial RF waveform. Signal sampling efficiency as a function of pyruvate and lactate excitation angle was simulated using two site exchange models. Dynamic imaging is demonstrated in a transgenic mouse model, and phantom validations of the RF pulse frequency selectivity were performed.